Effect of oxygen fraction on airway rescue: a computational modelling study. (July 2020) - Laviola, Marianna; Niklas, Christian; Das, Anup; Bates, Declan G.; Hardman, Jonathan G.
Abstract: Background: During induction of general anaesthesia, patients frequently experience apnoea, which can lead to dangerous hypoxaemia. An obstructed upper airway can impede attempts to provide ventilation. Although unrelieved apnoea is rare, it continues to cause deaths. Clinical investigation of management strategies for such scenarios is effectively impossible because of ethical and practical considerations. Methods: A population-representative cohort of 100 virtual ( in silico ) subjects was configured using a high-fidelity computational model of the pulmonary and cardiovascular systems. Each subject breathed 100% oxygen for 3 min and then became apnoeic, with an obstructed upper airway, during induction of general anaesthesia. Apnoea continued throughout the protocol. When arterial oxygen saturation ( S ao 2 ) reached 20%, 40%, or 60%, airway obstruction was relieved. We examined the effect of varying supraglottic oxygen fraction ( F o 2 ) on the degree of passive re-oxygenation occurring without tidal ventilation. Results: Relief of airway obstruction during apnoea produced a single, passive inhalation (caused by intrathoracic hypobaric pressure) in all cases. The degree of re-oxygenation after airway opening was markedly influenced by the supraglottic F o 2, with a supraglottic F o 2 of 100% providing significant and sustained re-oxygenation (post-rescue P ao 2 42.3 [4.4] kPa, when the airway rescue occurred after desaturation to S ao 2 60%). Conclusions: Supraglottic oxygen supplementation before relieving upper airway obstruction improves the effectiveness of simulated airway rescue. Management strategies should be implemented to assure a substantially increased pharyngeal F o 2 during difficult airway management.